STABILISASI TANAH LEMPUNG LUNAK DENGAN KAPUR PADA KONDISI KADAR AIR LAPANGAN - Yulian Firmana Arifin; Markawie Markawie (Universitas Lambung Mangkurat, 2013)
This paper discusses the soft clay soil stabilization with lime on the condition of the water content of the field. The sample used is soft clay of Marabahan, Barito Kuala, South Kalimantan. The water content of the sample is initially 76.2%. Samples were mixed with natural limestone that has been crushed and screened through a sieve No. 20 the percentage of 4, 8, 12, 16, and 20 percent based on the dry weight of the sample. Samples were mixed with lime cured for 7 and 14 days. Some of the tests performed in the laboratory include testing soil plasticity, direct shear tests, unconfined compression test, vane shear test, consolidation, and CBR. The results showed a decrease in the values of soil plasticity (liquid limit and plasticity index) and soil compression parameters (cc and cs) with the increased percentage of lime. While the values of cohesion, friction angle in, qu and qr, and CBR increases with increasing percentage of lime. The results also showed that the curing time effect on soil parameters were mixed lime.